The impact of perceived leadership quality, moral stress and participation on turnover intentions in ECEC sector - Cecilia Heilala; Marina Lundkvist; Nina Santavirta; Mirjam Kalland (Journal of Early Childhood Education Research, 2024)
The aim of this study was to investigate how perceived leadership quality, moral stress and participation are related to turnover intentions in early childhood education and care (ECEC). The theoretical framework was based on mentalizing leadership, participation, and moral stress. The data were collected via a survey (N = 332). The results showed that the ECEC staff were on average quite content with the quality of leadership and participation. Their turnover intentions and moral stress were moderate on average. However, the staff groups differed statistically significantly, with the ECEC nurses scoring lower on leadership satisfaction and participation, and higher on moral stress and turnover intentions than the teachers and leaders. This suggests that we need to develop a way of recognizing stressors at earlier stages, as well as handling them in time before they grow too large. For this, a functioning leadership that promotes reflection and participation is crucial.